2005
DOI: 10.1016/j.jtcvs.2004.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with an adenosine A1 receptor agonist and lidocaine: A possible alternative to myocardial ischemic preconditioning

Abstract: We conclude that activating adenosine A1 receptor subtype with CCPA and concomitantly modulating sodium fast channels with lidocaine was comparable with ischemic preconditioning and might offer a new therapeutic window to minimize myocardial damage during surgical ischemia and reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
(61 reference statements)
0
10
0
2
Order By: Relevance
“…In contrast, fifty-eight percent (58%) of saline controls died from ventricular fibrillation (Canyon and Dobson, 2004). In another study, the adenosine A 1 agonist 2-chloro-N6-cyclopentyladenosine (CCPA) was substituted for adenosine, and the CCPA-lidocaine combination showed remarkable infarct size reduction of over 80%, which was equivalent to that of ischemic preconditioning itself (Canyon and Dobson, 2005). In 2006, Canyon and Dobson showed using 31 P nuclear magnetic resonance (NMR) that the protective effects of AL constant infusion therapy were expressed as preservation of high-energy phosphates (ATP, PCr) in the area-at-risk of the left ventricle, and this was explained by a down-regulation of the myocardium during ischemia (Canyon and Dobson, 2006).…”
Section: Adenosine Lidocaine and Mg2+ (Alm™): A More Natural Way Tomentioning
confidence: 99%
“…In contrast, fifty-eight percent (58%) of saline controls died from ventricular fibrillation (Canyon and Dobson, 2004). In another study, the adenosine A 1 agonist 2-chloro-N6-cyclopentyladenosine (CCPA) was substituted for adenosine, and the CCPA-lidocaine combination showed remarkable infarct size reduction of over 80%, which was equivalent to that of ischemic preconditioning itself (Canyon and Dobson, 2005). In 2006, Canyon and Dobson showed using 31 P nuclear magnetic resonance (NMR) that the protective effects of AL constant infusion therapy were expressed as preservation of high-energy phosphates (ATP, PCr) in the area-at-risk of the left ventricle, and this was explained by a down-regulation of the myocardium during ischemia (Canyon and Dobson, 2006).…”
Section: Adenosine Lidocaine and Mg2+ (Alm™): A More Natural Way Tomentioning
confidence: 99%
“…To explain this cardioprotective effects, it was reported that this effects are due to reduction in ventricular arrhythmias (Canyon and Dobson 2004;Canyon and Dobson 2005), decreased myocardial dysfunction (Wang et al 2007;Ebel et al 2001), reduction in phosphate waste (Dias et al 2004;Canyon and Dobson 2006), and in infarct size (Hinokiyama et al 2003;Canyon and Dobson 2005) and apoptosis (Kaczmarek et al 2009). Interestingly, these cardioprotective effects have also been observed in patients undergoing on-pump coronary bypass grafting surgery and during pediatric cardiac surgery (Rinne and Kaukinen 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Important endogenous protective mechanisms include adenosine production, opening of ATP-sensitive potassium channels (KATP), release of nitric oxide, etc. [105,106]. Ischemia induces release of autocoids that activate complex intracellular signalling pathways some of which interconnect at the level of the mitochondria.…”
Section: Pharmacologic Approachmentioning
confidence: 99%